2015
DOI: 10.1111/coa.12504
|View full text |Cite
|
Sign up to set email alerts
|

Management of paediatric otogenic cerebral venous sinus thrombosis: a systematic review

Abstract: Conservative otological surgery with the combination of anticoagulation was the most common treatment modality found in the group of patients with good clinical outcome. However, given the current low level of evidence, a multicentre collaborative study is needed to help establish the optimum surgical approach and the role of anticoagulation in managing paediatric otogenic CVST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 46 publications
1
47
0
1
Order By: Relevance
“…Only one literature review has been published on the management of paediatric OLST but without specifically focusing on Fusobacterium infections. Based on our experience and in accordance with the European Pediatric Neurology Society which published in 2012 specific guidelines on the management of paediatric cerebral venous thrombosis, a management scheme for Fusobacterium acute mastoiditis with thrombosis is proposed herein (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Only one literature review has been published on the management of paediatric OLST but without specifically focusing on Fusobacterium infections. Based on our experience and in accordance with the European Pediatric Neurology Society which published in 2012 specific guidelines on the management of paediatric cerebral venous thrombosis, a management scheme for Fusobacterium acute mastoiditis with thrombosis is proposed herein (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis of the cerebral sinuses impedes blood flow and causes increased venous pressure which in turn results in increased ICP. In some cases,retrograde venous pressure decreases cerebral blood flow causing cerebral ischemia and infarction . Clinical features can be subtle and nonspecific, such as ear pain, fever, headache, irritability, and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…Prothrombotic condition was reported in 20% of patients with CSVT in a study by Ichord et al, and in the same study, MTHFR mutation was found in 7% of patients. Wong et al studied 190 patients with otogenic CSVT,only 50 patients were tested for thrombophilia and 28 of patients tested (56%) were found to have an abnormality. MTHFR mutation was found in five of these patients (10%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations